Kajian Persentase Ruta Pengguna Sanitasi dan Air Bersih Layak sebagai Standar Kesehatan Level Kabupaten Gorontalo Utara - Inzih Mohune; Dewi Wahyuni K. Baderan; Fitryane Lihawa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Access to adequate sanitation services and safe drinking water is a fundamental need that influences public health and sustainable development. This study analyzes the percentage of households in Gorontalo Utara Regency with access to adequate sanitation and safe drinking water from 2021 to 2023, linking it to WHO health standards. The results show an increase in access to adequate sanitation from 79.03% in 2021 to 81.80% in 2022, although there was a slight decline to 81.37% in 2023. Meanwhile, access to safe drinking water showed a more positive trend, rising from 86.23% in 2021 to 90.14% in 2023. This improvement reflects the success of government programs in enhancing basic infrastructure and raising community awareness. However, challenges remain in reaching approximately 10% of households still lacking access, particularly in remote areas. According to WHO, access to adequate sanitation and safe drinking water significantly reduces the risk of waterborne diseases such as diarrhea, cholera, and typhoid. This study highlights the importance of sustainable approaches to improving service coverage, such as developing inclusive infrastructure, educating communities on the importance of clean and healthy living behaviors, and strengthening the role of local institutions. In conclusion, although Gorontalo Utara has made significant progress, sustained efforts are needed to achieve universal access to sanitation and safe drinking water, as mandated by the SDGs.